1984
DOI: 10.1172/jci111496
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for size and charge permselectivity of rat ascending colon. Effects of ricinoleate and bile salts on oxalic acid and neutral sugar transport.

Abstract: A bbstract. We have measured unidirectional transmural fluxes of oxalate and neutral sugars across rat ascending colon in vitro, under short-circuit conditions, to characterize permeability barriers selective for size and charge. Ionic oxalate appears to be transported preferentially to sodium oxalate. Mucosal addition of taurocholate (1 mM), deoxycholate (1 mM), or ricinoleate (1 mM) increased bidirectional oxalate fluxes, and the ricinoleate effects were independent of medium calcium. Bidirectional fluxes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…There may even be species variation in the presence of these transporters, since three studies in the rat colon found oxalate transport to be nonsaturable (8-10) (see above for potential pitfalls in these studies), although a fourth study claimed active transport (20). Further, present evidence indicates that bile acids and fatty acids, which increase oxalate absorption in the colon, probably do so by causing a nonspecific increase in permeability (10,11,(20)(21)(22), and probably at the tight junction (23) rather than affecting a specific transport process. Bile acids and long-chain fatty acids do block NaCl absorption and induce electrogenic Cl secretion, however, which are transcellular, carrier-mediated processes (24)(25)(26).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…There may even be species variation in the presence of these transporters, since three studies in the rat colon found oxalate transport to be nonsaturable (8-10) (see above for potential pitfalls in these studies), although a fourth study claimed active transport (20). Further, present evidence indicates that bile acids and fatty acids, which increase oxalate absorption in the colon, probably do so by causing a nonspecific increase in permeability (10,11,(20)(21)(22), and probably at the tight junction (23) rather than affecting a specific transport process. Bile acids and long-chain fatty acids do block NaCl absorption and induce electrogenic Cl secretion, however, which are transcellular, carrier-mediated processes (24)(25)(26).…”
Section: Discussionmentioning
confidence: 80%
“…Until recently most investigators had concluded that oxalate was absorbed by a passive, noncarrier-mediated pathway and that increased absorption resulted from increased passive permeability and/or increased solubility of oxalate (2)(3)(4)(7)(8)(9)(10)(11)(12)(13)(14). Hatch et al (15), SITS),' which suggests an anion exchange process on the brush border.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are consistent with previous findings indicating an important role of passive oxalate absorption in the intestine. 25,26 Nevertheless, we cannot exclude the possibility that a component of transcellular oxalate absorption was not detected because of the absence of a critical substrate or regulatory factor under the conditions of our experiments. Indeed, a component of active transcellular oxalate absorption was identified in the rabbit colon on the basis of sensitivity of oxalate absorptive flux to metabolic inhibitors and the disulfonic stilbene SITS.…”
Section: Discussionmentioning
confidence: 84%
“…However, it appears likely that both increased solubility of oxalate in intraluminal water together with the enhanced permeability of colonic mucosa to soluble oxalate play complementary roles which together result in excessive colonic absorption of dietary oxalate following RYGB. Numerous studies have shown that fatty acids alter both the passive and active movements of electrolytes in both in vivo [1-3, 12, 21, 22] and in vitro [5,28,32,38] intestinal preparations. In addition, malabsorbed fat reaching colonic mucosa as a consequence of a number of gastrointestinal diseases has long been acknowledged to be the underlying cause of Enteric Hyperoxaluria [16,17].…”
Section: High Dietary Fat Promotes Changes In the Movements Of Oxalatmentioning
confidence: 99%